The Regulator Regulated: A Genealogy of the Pakistani Broadcast Media and its State of 'Double Capture' in the Post-Musharraf Era. (December 2019) - Akhtar, Asif
This article traces a genealogy of regulatory and other tactics through which the Pakistani broadcast media is controlled, comparing the colonial context of the development of these tactics with the postcolonial circumstances of their re-deployment. Archival research into the East India Company's documents from the turn of the nineteenth century uncovers the development of regulatory regimes referred to as Censorship, Self-Regulation, and Licensing, in addition to extra-legal techniques. The article argues that colonial tactics still form key components of Pakistan's postcolonial broadcast regulations. However, in the past, one regime was replaced by another in a linear progression; today these regulatory techniques appear concomitantly stacked, selectively deployable and enfolded within an expanding array of extralegal techniques. The article seeks to move beyond conceptions of 'regulatory capture' or 'media capture' by applying the Deleuzian concept of 'double capture': in the case of the Pakistani broadcast media, the government regulator (and to some extent the government itself) is captured by 'media power' in the same instance that the media assemblage itself becomes subject to 'state capture' through extralegal means. Part one focuses on the decades when the colonial state first regulated newsprint (1780–1823), tracing the development from extralegal controls to a succession of legal regulations through which Company administrators could regulate – rather than be regulated by – colonial newsprint. Part two considers the paradoxical situation in Pakistan's contemporary broadcast regulations (2002–2018), where PEMRA seems powerless to regulate the media, yet the media is subject to a 'double capture' through a combination of legal and extralegal modes of control.